Rozwój małych i średnich przedsiębiorstw w województwie pomorskim - Ćwikliński, Henryk (The Results of 2006 Research on SMEs Activity in Pomeranian Region, 2008)
Only every 11th company expected either no profit or a loss in 2006. A clear majority of studied companies operated in the private sector. Foreign capital involvement was identified in only every 13th company. Only 1% of SMEs declare the readiness to adopt a strategic change, while "strong expansion" is the declared intention of 8.7% of them. About half of all SMEs were of the opinion that the level of demand corresponds to their production capacity or is slightly smaller. Nearly half of SMEs in Pomerania are afraid of local competition, and only 13.3% of companies are afraid of competition from abroad. Nearly half of the studied companies did not perceive any threat from the opening of the EU market. Average level of employment in one SME amounts to about 35 people. People with vocational education have a dominant share among the employed (in average they constitute 36% of the total number of employees). In average every sixth employee of a SME is a graduate of higher educational institutions. In over 80% of SMEs the employees are involved in the process of upgrading their professional skills, most often, however, in the process of practical experience (learning by doing). Only 5% of all SMEs have their own research and development units. Over 93% of all SMEs do not have any patent rights, and 98% do not aspire to acquire them. 81% of all SMEs do not use any trade marks. 63% of all SMEs invest in purchases of machinery, technical equipment and tools and nearly a half in the purchase of transport equipment. It is possible to enumerate the following factors, which constitute at least a significant barrier to the development of companies: instability and obscurity of regulations, high level of taxation, bureaucracy, lack of finance for investment and difficulty in finding appropriate employees. Over half of SMEs in Pomerania declared that they do not have difficulties in finding appropriate workers. SMEs as a majority, do not have problems with getting bank loans. Nearly 60% of SMEs look for further partners for co-operation, principally to reduce costs (about 34%) or to enter local sales markets (over 29%).(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 227-241